2021
DOI: 10.3389/fneur.2020.617276
|View full text |Cite
|
Sign up to set email alerts
|

Continuity of Care During COVID-19 Lockdown: A Survey on Stakeholders' Experience With Telerehabilitation

Abstract: Objective: To explore professionals', adult patients', and children's caregivers' perception and satisfaction with telerehabilitation during COVID-19 lockdown.Design: An observational transversal study on a web-based survey was conducted in order to explore participants' perception and satisfaction of telerehabilitation during COVID-19 lockdown.Setting: The study was conducted at our Outpatient Neurorehabilitation Service.Subjects: All rehabilitation professionals, adult patients, and children's caregivers who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 67 publications
(76 reference statements)
2
19
0
3
Order By: Relevance
“…Moreover, the results correlate with previous findings ( Lotan et al, 2021 ), where parents were delighted with the program’s adaptability to the person with RTT and her daily routines. Levels of total satisfaction expressed by parents within the present project are coherent with previous reports available in the literature for other populations with disabilities ( Assenza et al, 2020 ; Tanner et al, 2020 ; Caprì et al, 2021 ).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Moreover, the results correlate with previous findings ( Lotan et al, 2021 ), where parents were delighted with the program’s adaptability to the person with RTT and her daily routines. Levels of total satisfaction expressed by parents within the present project are coherent with previous reports available in the literature for other populations with disabilities ( Assenza et al, 2020 ; Tanner et al, 2020 ; Caprì et al, 2021 ).…”
Section: Discussionsupporting
confidence: 90%
“…These findings suggest that both parents’ and children’s age could affect the satisfaction with telerehabilitation services. Furthermore, these authors ( Assenza et al, 2020 ), as well as others ( Utidjian and Abramson, 2016 ; Brophy, 2017 ; Tanner et al, 2020 ), reported that the level of experience in technology use could be a significant barrier to telerehabilitation, affecting the client’s satisfaction. Due to the scarcity of existing knowledge on variables affecting parental satisfaction with telerehabilitation services for children with disabilities, several articles reported a high level of parents’ satisfaction whose children received remote therapy intervention ( Hinton et al, 2017 ; Assenza et al, 2020 ; Camden et al, 2020 ; Sanders et al, 2020 ; Tanner et al, 2020 ; Caprì et al, 2021 ).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…The heterogeneity nature of managing aphasia online might have also made it a difficult process for PWA, their carers, and clinicians to adjust [40]. Nevertheless, telepractice has been utilized as an effective alternative to in-person aphasia therapy and some recent reports have suggested that it is a viable method of service delivery for PWA during this unprecedented crisis, with endorsement of a high level of satisfaction from rehabilitation professionals and adult patients [41,42].…”
Section: Remote Services To Chronic Pwamentioning
confidence: 99%